Determination, Modeling and Evaluation of Kinetics of 223Ra Sorption on Hydroxyapatite and Titanium Dioxide Nanoparticles - Suchánková, Petra; Kukleva, Ekaterina; Štamberg, Karel; Nykl, Pavel; Sakmár, Michal; Vlk, Martin; Kozempel, Ján (Materials (Basel, Switzerland), 2020)
Sorption kinetics of radium on hydroxyapatite and titanium dioxide nanomaterials were studied. The main aim of the current study was to determine the rate-controlling process and the corresponding kinetic model, due to the application of studied nanomaterials as α-emitters' carriers, and to assess the sorption properties of both materials from the radiopharmaceutical point of view by time regulated sorption experiments on the nanoparticles. Radium-223 was investigated as radionuclide used in targeted alpha particle therapy as an in vivo generator. It was found that the controlling process of the 223Ra sorption kinetics was the diffusion in a reacted layer. Therefore, parameters like particle size, their specific surface area, contact time and temperature played important role. Moreover, the composition of liquid phase, such as pH, the concentration of 223Ra, ionic strength, the presence of complexation ligands, etc., had to be considered. Experiments were conducted under free air conditions and at pH 8 for hydroxyapatite and pH 6 for titanium dioxide in Britton-Robinson buffer. Initial 223Ra concentration was in the range from 10-11 to 10-12 mol/L. It was found that sorption kinetics was very fast (more than 90% in the first hour) in the case of both nanomaterials, so they can be directly used for efficient radium sorption.
Keywords: titanium dioxide; ion sorption kinetics; hydroxyapatite; kinetic models; nanoparticles; radium-223